Accuracy and reliability of PBV ASPECTS, CBV ASPECTS and NCCT ASPECTS in acute ischaemic stroke: a matched-pair analysis. Issue 6 (December 2021) - Potreck, Arne; Falbesaner, Alina; Seker, Fatih; Weyland, Charlotte S; Mundiyanapurath, Sibu; Heiland, Sabine; Bendszus, Martin; Pfaff, Johannes AR
Background and purpose: To investigate the reliability and accuracy of Alberta Stroke Program Early Computed Tomography Scores (ASPECTS) derived from flatpanel detector computed tomography pooled blood volume maps compared to non-contrast computed tomography and multidetector computed tomography perfusion cerebral blood volume maps. Methods: ASPECTS from pooled blood volume maps were evaluated retrospectively by two experienced readers for 37 consecutive patients with acute middle cerebral artery (MCA) M1 occlusion who underwent flatpanel detector computed tomography perfusion imaging before mechanical thrombectomy between November 2016 and February 2019. For comparison with ASPECTS from non-contrast computed tomography and cerebral blood volume maps, a matched-pair analysis according to pre-stroke modified Rankin scale, age, stroke severity, site of occlusion, time from stroke onset to imaging and final modified thrombolysis in cerebral infarction (mTICI) was performed in a separate group of patients who underwent multimodal computed tomography prior to mechanical thrombectomy between June 2015 and February 2019. Follow-up ASPECTS were derived from either non-contrast computed tomography or from magnetic resonance imaging (in seven patients) one day after mechanical thrombectomy. Results: Interrater agreement was best for non-contrast computed tomography ASPECTS (w-kappa = 0.74, vs. w-kappa = 0.63 for cerebral blood volume ASPECTS and w-kappa = 0.53 for pooled blood volume ASPECTS). Also, accuracy, defined as correlation between acute and follow-up ASPECTS, was best for non-contrast computed tomography ASPECTS (Spearman ρ = 0.86 (0.65–0.97), P  < 0.001), while it was lower and comparable for pooled blood volume ASPECTS (ρ = 0.58 (0.32–0.79), P  < 0.001) and cerebral blood volume ASPECTS (ρ = 0.52 (0.17–0.80), P  = 0.001). It was noteworthy that cases of relevant infarct overestimation by two or more ASPECTS regions (compared to follow-up imaging) were observed for both acute pooled blood volume and cerebral blood volume ASPECTS but occurred more often for acute pooled blood volume ASPECTS (25% vs. 5%, P  = 0.02). Conclusion: Non-contrast computed tomography ASPECTS outperformed both pooled blood volume ASPECTS and cerebral blood volume ASPECTS in accuracy and reliability. Importantly, relevant infarct overestimation was observed more often in pooled blood volume ASPECTS than cerebral blood volume ASPECTS, limiting its present clinical applicability for acute stroke imaging.